INTEGRASI PENDIDIKAN GIZI DALAM KURIKULUM SEKOLAH: MANFAAT DAN IMPLEMENTASI - Aslan Aslan; Naba Naba (Jurnal Kesehatan, 2025)
Integrating nutrition education into the school curriculum is an important step in improving students‘ health and well-being. This study examines the benefits and implementation of nutrition education in schools. The results show that effective nutrition education can increase students’ knowledge of balanced nutrition, help them make better food choices, and reduce the risk of nutrition-related diseases such as obesity and diabetes. The implementation involves practical activities, such as cooking and gardening, which help students apply theory to everyday life. In addition, school policies that support healthy food can reinforce lessons taught in the classroom. Therefore, nutrition education in the school curriculum not only improves students' nutrition and health but also creates positive synergies between schools, families, and communities.